2005
DOI: 10.1038/nn1485
|View full text |Cite
|
Sign up to set email alerts
|

Loss of mammalian Sprouty2 leads to enteric neuronal hyperplasia and esophageal achalasia

Abstract: We report here that loss of the Sprouty2 gene (also known as Spry2) in mice resulted in enteric nerve hyperplasia, which led to esophageal achalasia and intestinal pseudo-obstruction. Glial cell line-derived neurotrophic factor (GDNF) induced hyperactivation of ERK and Akt in enteric nerve cells. Anti-GDNF antibody administration corrected nerve hyperplasia in Sprouty2-deficient mice. We show Sprouty2 to be a negative regulator of GDNF for the neonatal development or survival of enteric nerve cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 10 publications
3
104
0
Order By: Relevance
“…T Ayada et al bud-derived epithelial tubes (Basson et al, 2005(Basson et al, , 2006, mSprouty2 regulates embryonic lung branching morphogenesis (Tefft et al, 1999) as well as motor nerve networks in digestive organs (Taketomi et al, 2005). Angiogenesis is another form of branching morphogenesis and the overexpression of mSprouty4 has been shown to inhibit branching and sprouting of small vessels (Lee et al, 2001).…”
Section: Sprouty4 Inhibits Pip 2 Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…T Ayada et al bud-derived epithelial tubes (Basson et al, 2005(Basson et al, , 2006, mSprouty2 regulates embryonic lung branching morphogenesis (Tefft et al, 1999) as well as motor nerve networks in digestive organs (Taketomi et al, 2005). Angiogenesis is another form of branching morphogenesis and the overexpression of mSprouty4 has been shown to inhibit branching and sprouting of small vessels (Lee et al, 2001).…”
Section: Sprouty4 Inhibits Pip 2 Hydrolysismentioning
confidence: 99%
“…It is notable that enteric nerve development is regulated by GDNF and endothelin-3 (Angrist et al, 1996;Hempstead, 2004). Therefore, the enteric nerve dysplasia phenotype of Sprouty2 KO mice may be partly explained by hypersignaling of ET-3 (Taketomi et al, 2005). As the physiological role of GPCR ligand-induced PIP 2 hydrolysis has not been well characterized, Sprouty KO mice could be a useful tool for defining this.…”
Section: Sprouty4 Inhibits Pip 2 Hydrolysis T Ayada Et Almentioning
confidence: 99%
“…Also, FGF2 (basic FGF) is an essential component of the culture media used to stimulate growth of both ENS progenitor cells and neural stem cells in vitro and maintains cells in a continuously expanding state (29,38). Finally, the mice mutant for the FGF receptor antagonist Sprouty2 exhibits ENS hyperganglionosis (39). Taken together, these findings suggest roles for FGFs in ENS development, which remain to be explored.…”
Section: Sox2 As a Potential Marker Of Proliferative And Stem Cell Pomentioning
confidence: 99%
“…Furthermore, overexpression studies have revealed that cells expressing Spry proteins exhibit reduced migration, proliferation, invasion, and differentiation (15, 19, 26 -31). Recent reports, including murine knock-out studies of Spry1 and Spry2, have demonstrated that Spry proteins not only attenuate FGF-and EGF-mediated p42/44 ERK activation, but also inhibit signaling induced by glial cell line-derived neurotrophic growth factor, c-kit, insulin, platelet-derived growth factor, nerve growth factor, hepatocyte growth factor, and vascular endothelial growth factor (VEGF) (19,29,(32)(33)(34)(35)(36)(37).…”
mentioning
confidence: 99%